Adolescent strategies for dealing with mental and moral problems are based on the perception of the Psalms - Noti, Yetri Anisa; Naibaho, Lamhot; Rantung, Djoys Anneke (International Journal Labs, 2023)
Adolescence is a transitional period from childhood to adulthood. Adolescence is closely related to self-discovery and they find a lot of offers from the surrounding environment in the form of character and personality traits that they can try depending on their perception and direction. Religious adolescents have guidelines in their lives, religious adolescents will place God as the centre of their lives, determine that everything must be based on the laws that God gives, and all teenagers' actions must aim not to violate the laws given by God. The method used in this research uses qualitative research methods with literature studies. The researcher reviewed and used various information and previous research, as well as conducted textual, contextual, and biblical implementation research on the book of Psalms by selecting or correlating verses related to mental and moral problems faced by the writers of Psalms when they experienced mental and moral inner turmoil from what they experienced in the lives written in the book of Psalms. Christian teenagers should live in spiritual and mental closeness to God. The best way is to not hang out with people who have moral problems. Not walking and sitting with the wicked. Be willing to accept the logical consequences of being separated from those who do not practice God's goodness.